Investigation of Optimum Polymerization Conditions for Synthesis of Cross-Linked Polyacrylamide-Amphoteric Surfmer Nanocomposites for Polymer Flooding in Sandstone Reservoirs - A. N. El-hoshoudy; S. E. M. Desouky; M. Y. Elkady; A. M. Alsabagh; M. A. Betiha; S. Mahmoud (International Journal of Polymer Science)
Currently enhanced oil recovery (EOR) technology is getting more attention by many countries since energy crises are getting worse and frightening. Polymer flooding by hydrophobically associated polyacrylamides (HAPAM) and its modified silica nanocomposite are a widely implemented technique through enhanced oil recovery (EOR) technology. This polymers class can be synthesized by copolymerization of acrylamide (AM), reactive surfmer, functionalized silica nanoparticles, and a hydrophobic cross-linker moiety in the presence of water soluble initiator via heterogeneous emulsion polymerization technique, to form latexes that can be applied during polymer flooding. Chemical structure of the prepared copolymers was proven through different techniques such as Fourier transform infrared spectroscopy (FTIR), and nuclear magnetic spectroscopy (1H&13C-NMR), and molecular weight was measured by gel permeation chromatography. Study of the effects of monomer, surfmer, cross-linker, silica, and initiator concentrations as well as reaction temperature was investigated to determine optimum polymerization conditions through single factor and orthogonal experiments. Evaluation of the prepared copolymers for enhancing recovered oil amount was evaluated by carrying out flooding experiments on one-dimensional sandstone model to determine recovery factor.